STUDENTS’ IMPROVEMENT IN LISTENING COMPREHENSION THROUGH DIGITAL NARRATIVE MEDIA - Yuanisa, Falen (English Education and Applied Linguistics Journal (EEAL Journal), 2022)
Listening is a skill that must be acquired in learning English. However, there are difficulties that are felt by the students when they are learning listening. The distractions inside and outside the classroom make the learning process become ineffective. Because of that, Digital Narrative Media was considered for teaching listening comprehension at one class of eleventh grade in one of Senior High School in Garut. This research aimed to improve students’ listening comprehension. This research used a quantitative method and pre- experimental as the design for the research. The researcher chose the participants from one class of eleventh grade in one of Senior High School in Garut. The research sample consisted of 30 students. The researcher uses pre-test and post-test for collecting data and then analyzed the data by statistical analysis. The research findings showed that the students‘pre- test mean score was 67.50 to be 80.00 in the post-test. The t-test analysis showed that Sig. (2-tailed) is 0.000 which is smaller than α = 0.05. It means that there was a significant difference of students‘ listening comprehension before and after using the Digital Narrative Technique. In conclusion, Digital Narrative Technique was effective to improve students‘ listening comprehension.